2022
DOI: 10.1002/cam4.5030
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent physical activity versus modified behavioral activation in adolescent and young adult cancer patients with psychological distress: A randomized, controlled pilot trial

Abstract: Background More than 80% of adolescent and young adult cancer patients (AYACPs) experienced psychological distress. Physical activity and behavioral activation are effective to relieve the psychological distress in AYACPs. Methods Participants aged 15–39 years diagnosed with malignant tumors were included. A total of 143 eligible AYACPs were randomly assigned to three groups. The treatment‐as‐usual group (N = 48) received routine care, the physical activity group (N = 47) received 8 weeks of physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These studies were designed to provide symptomatic relief of AYA patients from anxiety, depression, sleep disturbances, and pain. Overall, we have observed that PA, MBSR, massage and BWL were found effective in relieving chemotherapy induced fatigue, anxiety and depression compared to controls [22,25,27,41].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These studies were designed to provide symptomatic relief of AYA patients from anxiety, depression, sleep disturbances, and pain. Overall, we have observed that PA, MBSR, massage and BWL were found effective in relieving chemotherapy induced fatigue, anxiety and depression compared to controls [22,25,27,41].…”
Section: Discussionmentioning
confidence: 71%
“…PA, massage, BWL and yoga studies reported improved sleep quality [31,38,41]. However, there is limited research on PA use in AYA [25,26] and survivorship issues [9]. Several barriers have been identified to conduct research on PA in AYAC [42] including schedule-related barriers (time, vacations, visitors), health-related barriers (pain, fatigue) and unfavorable circumstances like weather and lack of motivation that may limit PA and exercise use in AYAC [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is not only known as an evidence-based treatment for depression [42] but is also known to be related to behavioral activation therapy for depression, which induces behavioral attitudes and healthy behaviors [43]. Behavioral activation is targeted at reducing behavioral inertia and avoidance, which often accompanies depression, by increasing daily activities [44].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven trials investigated the impact of stress-specific interventions on cortisol, six of which (Antoni et al, 2009;Banasik et al, 2011;Dodds et al, 2015;Hoyt et al, 2021;Hsiao et al, 2012;Penedo et al, 2021) used log-transformed data to analyse cortisol, and the remaining researches (Black et al, 2017;Cruess et al, 2000;Li et al, 2023;Mirmahmoodi et al, 2020;Vadiraja et al, 2009) displayed the cortisol level with raw data. As shown in Figure 6, except for morning cortisol using raw data, the analysis indicated that stress-specific interventions did not reduce the cortisol level at different periods ( p > .05).…”
Section: Cortisolmentioning
confidence: 99%